2019
DOI: 10.1111/cts.12631
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Global Drug Development Pathways and Postmarketing Safety in Japan: Local Studies May Reduce Drug‐Related Deaths

Abstract: Recent International Conference on Harmonization (ICH) guidelines provide pharmaceutical companies with regulatory justifications to pursue various global drug‐development pathways, in some of which “local” dose‐ranging and/or pivotal phase III studies are skipped. We examined the association between the clinical development pathway and postmarketing safety in Japan for 177 new molecular entities approved between 2004 and 2013 focusing on dose setting histories for each drug. The risk of drug‐related deaths wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yamada et al (2010) indicated the benefit of access to safety data accumulated in other countries as a trade-off for delay in access to new drugs in Japan [32]. Okubo et al (2019) reported that drugs developed under a bridging strategy tended to show lower risks, and that local clinical studies may play a substantial role in achieving optimization of post-marketing drug use [24]. In addition, a case-by-case discussion with the PMDA may support flexible drug development and allow regulators making a flexible decision upon drug approval.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (2010) indicated the benefit of access to safety data accumulated in other countries as a trade-off for delay in access to new drugs in Japan [32]. Okubo et al (2019) reported that drugs developed under a bridging strategy tended to show lower risks, and that local clinical studies may play a substantial role in achieving optimization of post-marketing drug use [24]. In addition, a case-by-case discussion with the PMDA may support flexible drug development and allow regulators making a flexible decision upon drug approval.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the local development optimized to medical environments in Japan have provided important evidence and improved appropriate post-marketing use [26,27]. For example, the national health/medical insurance system in Japan allows patients to obtain approved drugs easily, therefore participating in clinical trials to receive non-approved drugs may not be attractive from risk and benefit perspective compared to approved drug treatment.…”
Section: Mrct May Become a Solution Of Development Initiation Lagmentioning
confidence: 99%